2010
DOI: 10.17221/85/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria in the environment of pig farms in the Czech Republic between 2003 and 2007

Abstract: ABSTRACT:In the Czech Republic, most mycobacterial infections in pigs are caused by the Mycobacterium avium complex (MAC) and potentially pathogenic mycobacteria (PPM) derived from the environment. This study was undertaken after the isolation of PPM from various components of the environment of pig herds between 1996 (Matlova et al., Veterinarni Medicina, 48, 2003. Between 2003 and 2007, a total of 1114 environmentally-derived samples from 24 farms were examined. After staining according to Ziehl-Neelsen, aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The rate of mycobacterial contamination ranged from 63 to 100% with the predominant isolate being M. a. hominissuis (82.1%), followed by M. fortuitum and M. gordonae (3.5%). This finding concurs with previous studies in which M. a. hominissuis was detected most frequently Krizova et al 2010). M. a. hominissuis as well as other PPM and environmentally saprophytic mycobacteria (which were also found in peat), can induce the development of tuberculous lesions in mesenteric lymph nodes in pigs Matlova et al 2005;Shitaye et al 2006).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The rate of mycobacterial contamination ranged from 63 to 100% with the predominant isolate being M. a. hominissuis (82.1%), followed by M. fortuitum and M. gordonae (3.5%). This finding concurs with previous studies in which M. a. hominissuis was detected most frequently Krizova et al 2010). M. a. hominissuis as well as other PPM and environmentally saprophytic mycobacteria (which were also found in peat), can induce the development of tuberculous lesions in mesenteric lymph nodes in pigs Matlova et al 2005;Shitaye et al 2006).…”
Section: Resultssupporting
confidence: 92%
“…Investigations into the external sources of infection causing the tuberculous lesions revealed that the primary source of MAC was peat fed as a supplement Trckova et al 2006a,b). Various species of PPM have been detected in peat with M. a. hominissuis the most often isolated Krizova et al 2010). In Germany, peat was also found to be a major source of mycobacteria in pigs as early as the mid-1970s (Engel et al 1978.…”
mentioning
confidence: 99%
“…a. hominissuis is a potential pathogen commonly occurring in the environment, above all in soil and water (Kazda et al, 2009;Kaevska and Hruska, 2010a,b;Krizova et al, 2010). It can infect humans, and is frequently isolated from children with peripheral lymphadenopathy (van Coppenraet et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the environment and infected animals remain the main reservoir for NTM including MAA (Kazda et al, 2009;Krizova et al, 2010)). Although various sources of infection in the environment exist (i.e.…”
Section: Discussionmentioning
confidence: 99%